ASPEK-ASPEK PERLOKUSI DALAM FILM SPY KARYA PAUL FEIG - DONGALEMBA, RHODE MARGARETH (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research entitled ?Perlocutionary aspects in the film Spy by Paul Feig?. The analysis of this research focuses on the aspects of perlocutionary acts of utterances which are identified in the film Spy. This research contributes to the development of linguistics in the field of pragmatics especially the aspects of perlocutionary acts in the film ?Spy? by Paul Feig. The collected data are identified, classified, and analyzed descriptively in term of how the aspects of perlocutionary acts is performed in the film by using Leech?s theory (1983 : 203) about aspects of perlocutionary acts of utterances. The result of this research shows that the aspects of perlocutionary acts found in this film are 36 utterances which are bringing the hearer to learn that, persuade, encourage, irritate, frighten, amuse, get the hearer to do, inspire, impress, distract, get the hearer to think about, attract attention, and bore.      Keywords : pragmatics, speech act, perlocutionary acts, film.